Inhibition of bovine brain acetylcholinesterase by aluminum. - Moraes, M. S. [UNESP]; Leite, S. R. [UNESP] (My University, 1994)
We report the in vitro inhibitory effect of very low concentrations of aluminum salts (IC50 = 4.1 x 10(-12 M) on bovine brain acetylcholinesterase (AChE). The enzymatic assays were performed using acetylcholine bromide in a buffered pH 7.4 solution at 37 degrees C. The relevant enzyme interacting species is the Al3+ ion, whose concentrations were fixed at pM levels by a citrate metal ion buffer system. The IC50 demonstrates that Al3+ is a potent inhibitor of AChE.